A Study of the Relationship Between Teachers’ Motivation and Teachers’ Commitment at Experimental Middle School Affiliated to Yunnan Normal University - Mao, RuiTao; Watana Vinitwatanakhun (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
In this study, the prime target is to identify the relationship two variables of relationship which is teachers’ motivation and teachers’ commitment in the Experimental Middle School Affiliated to Yunnan Normal University. 114 full-time teachers participated in the study. They have all been certified in Experimental Middle School Affiliated to Yunnan Normal University in the 2021 academic. The average and standard deviation were used to analyze teachers' consciousness of teachers' motivation. It was found that teachers' perception of teachers' motivation was high (3.70) and another variable of teachers’ commitment also got a high score(3.71); To study the correlation between the two variables, The study used the Pearson Product Moment Correlation Coefficient method and data r =. 642, SIG. (two tailed) was. 002. The results show that teachers in target schools hold a relatively positive attitude towards teachers' motivation. Pearson correlation test’s results shows that there is a prominent correlation between the teachers' motivation and teachers' commitment in Experimental Middle School Attached to Yunnan Normal University.